1988
DOI: 10.1002/jlb.43.5.387
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Labeling of Resident Peritoneal Macrophages

Abstract: A novel method for labeling resident peritoneal macrophages (M phi) by injection of a dye into the peritoneal cavity is described. The dye, which fluoresces green, is selectively taken up by the resident M phi. Dye labeled cells can be further characterized by labeling of cell surface antigens with monoclonal antibodies (Mabs) and phycoerythrin conjugated second antibody. After such labeling with the Mabs F4/80 or Mac 1 the resident M phi were labeled by both the green dye and the red Mab markers, while recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…By the use of a specific linker technique, dye aggregates or particulates are formed and ingested by phagocytosis in vivo or in vitro without evidence of functional impairment [16,17]. This technique allows the quantity of intravascular monocytes that have become peritoneal macrophages within a specified period to be determined [16], as well as the quantity of polymorphonuclear leukocyte granulocytes migrating from the blood compartment into the peritoneum.…”
Section: Experimental Settingmentioning
confidence: 99%
“…By the use of a specific linker technique, dye aggregates or particulates are formed and ingested by phagocytosis in vivo or in vitro without evidence of functional impairment [16,17]. This technique allows the quantity of intravascular monocytes that have become peritoneal macrophages within a specified period to be determined [16], as well as the quantity of polymorphonuclear leukocyte granulocytes migrating from the blood compartment into the peritoneum.…”
Section: Experimental Settingmentioning
confidence: 99%
“…Previously, it has been demonstrated that PKH labelled cells grow normally in culture [14], react normally in cytotoxic assays [7,14] and that the incorporation of PKH does not physically weaken the membrane of the cells [15]. However, at higher concentrations there can be difficulties in the detection of cell surface antigens using flow cytometry [6].…”
Section: Discussionmentioning
confidence: 99%
“…The newer fluorescent labelling molecule PKH, which is incorporated into the lipid bilayer of cytoplasmic membranes, has been used for labelling a variety of cells, including peripheral lymphocytes [6], macrophages [7] and erythrocytes [8].…”
Section: Introductionmentioning
confidence: 99%
“…The prerequisites for using PKH26 for labelling of cells has been demonstrated in the previous study by many researchers that the incorporation of PKH dye does not physically weaken the membrane of the cells, does not interfere with the functions of the cells and appeared to be ideal for long-term tracking of cells. Animal studies revealed no toxicity of the PKH dye and no immune response appears to generate against labelled cells (Read et al, 1991;Slezak andHoran, 1989a, 1989b;Melnicoff et al, 1988). Most importantly, Johnsson et al (1997) had reported in their 'ex vivo PKH26-labelling of lymphocytes for studies of cell migration in vivo' study of this labelling dye was found to be retained within the labelled cells and not transferred to other cells.…”
Section: Fluorescence Microscopic Analysismentioning
confidence: 98%